The role of social support to increase the Confidence of the Deaf in the Difabel Study Council - Sri Maullasari (Journal of Advanced Guidance and Counseling, 2022)
Purpose - This study aims to determine the role of peer social support in increasing the self-confidence of the deaf in the Difabel Study Council.Method - This research is devoted to people with hearing impairment. The approach used in this study is a descriptive qualitative approach. Data collection method employed Interview and observation. The primary data sources are participants who are deaf, while the secondary data source is the administrator and participant Assembly studying the disabled. Technique for data analysis applied triangulation source. Social support is required by people with hearing impairment as an effort to suppress psychosocially.Result - The findings of this study state that the deaf perceives social support from their peers.Implication - Deaf fellows in the Difabel Study Council have an important role in social support because social support from friends makes them feel protected, and loved, and think more broadly that all humans are the same because, for the deaf.Originality - This research is presented concerning religious guidance services for deaf individuals.***Tujuan – Penelitian ini bertujuan untuk mengetahui peran dukungan sosial teman sebaya dalam meningkatkan rasa percaya diri penyandang tunarungu di Dewan Studi Difabel.Metode – Penelitian ini dikhususkan pada penyandang disabilitas pendengaran. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan deskriptif kualitatif. Metode pengumpulan data menggunakan wawancara dan observasi. Sumber data primer adalah peserta penyandang tunarungu, sedangkan sumber data sekunder adalah pengurus dan peserta majelis pengajian penyandang disabilitas. Teknik analisis data menggunakan triangulasi sumber. Dukungan sosial diperlukan oleh penyandang disabilitas pendengaran sebagai upaya menekan secara psikososial.Hasil - Temuan penelitian ini menyatakan bahwa penyandang tunarungu merasakan dukungan sosial dari teman sebayanya.Implikasi – Teman-teman tunarungu yang tergabung dalam Dewan Kajian Difabel mempunyai peran penting dalam dukungan sosial karena dukungan sosial dari teman membuat mereka merasa dilindungi, dan dicintai, serta berpikir lebih luas bahwa semua manusia itu sama karena bagi penyandang tunarungu.Orisinalitas - Penelitian ini disajikan mengenai layanan bimbingan keagamaan bagi penyandang tunarungu.